Bizarre tail weaponry in a transitional ankylosaur from subantarctic Chile - Soto-Acuna, Sergio; Vargas, Alexander O.; Kaluza, Jonatan; Leppe, Marcelo A.; Botelho, Joao F.; Palma-Liberona, Jose; Simon-Gutstein, Carolina; Fernandez, Roy A.; Ortiz, Hector; Milla, Veronica; Aravena, Barbara; Manriquez, Leslie M. E.; et al. (My University, 2021)
Armoured dinosaurs are well known for their evolution of specialized tail weapons-paired tail spikes in stegosaurs and heavy tail clubs in advanced ankylosaurs(1). Armoured dinosaurs from southern Gondwana are rare and enigmatic, but probably include the earliest branches of Ankylosauria(2-4). Here we describe a mostly complete, semi-articulated skeleton of a small (approximately 2 m) armoured dinosaur from the late Cretaceous period of Magallanes in southernmost Chile, a region that is biogeographically related to West Antarctica(5). Stegouros elengassen gen. et sp. nov. evolved a large tail weapon unlike any dinosaur: a flat, frond-like structure formed by seven pairs of laterally projecting osteoderms encasing the distal half ofthe tail. Stegouros shows ankylosaurian cranial characters, but a largely ancestral postcranial skeleton, with some stegosaur-like characters. Phylogenetic analyses placed Stegouros in Ankylosauria; specifically, it is related to Kunbarrasaurus from Australia(6) and Antarctopelta from Antarctica(7), forming a Glade of Gondwanan ankylosaurs that split earliest from all other ankylosaurs. The large osteoderms and specialized tail vertebrae in Antarctopelta suggest that it had a tail weapon similar to Stegouros. We propose a new clade, the Parankylosauria, to include the first ancestor of Stegouros-but not Ankylosaurus-and all descendants ofthat ancestor.
Keywords: None